Knowledge, attitude & practice of pregnant women about the role of periconceptional use of folic acid in three primary health care centers in Baghdad / AL-Russafa - Lateef, Walaa . N; Al-Hashimi, *Ban A. (AL-Kindy College Medical Journal, 2016)
Background: Folic acid (vitamin B9) is one of the important vitamins that are necessary for growth and development of the embryo and preventing the occurrence of congenital malformations which are one of the important health problems in the developing countries and the world as it has a direct effect on the affected babies, their families and the community. It affects an estimated 3% of newborns worldwide.Periconceptional supplementation with folic acid (before conception and during the first 12 weeks of pregnancy) was found to decrease many important types of these anomalies. Objectives: The aim of this study is to assess knowledge, attitude and practice of periconceptional use of folic acid in pregnant women who are attending antenatal care unit in three Primary Health Care Centers in Baghdad / AL-Russafa side. Type of the study: Descriptive cross-sectional study Patients and Methods: The study used a convenient sample technique for pregnant women who are attending antenatal care unit in three primary health care centers in Baghdad/ALـRussafa at the period from January to April 2014. The sample size was 200. Non-pregnant women were excluded. Results: a large proportion (86%) of pregnant women who had been interviewed knew about folic acid. 61% of them gained the information about it from doctors and 44.5% know its importance in protection from congenital anomalies. Although there was a good practice regarding folic acid supplementation during the current pregnancy; only 10% of them had used it in the proper time (at least one month before pregnancy to the end of the first trimester). It has been found that the largest rate of its use was in the second month (28%), Still 22% of them realize that it must be taken before pregnancy. Conclusion: From 200 pregnant women interviewed in the current study, the majority knew about folic acid but nearly only half of them states its importance in protection from congenital anomalies. Most of the women usedfolic acid in the current pregnancy on a daily bases and take it as pure folic acid. Although some of the pregnant women were aware about the proper time of taking folic acid, only few took it before pregnancy. Doctors were the main source of information.